Evaluation of West African Agricultural Productivity Programme in the Institute of Agricultural Research and Training Adopted Villages - Anjolaoluwa Ore Fadairo; Margaret Olayemi Oyedokun; Adeniyi Amusat; Lucia Omobolanle Ogunsumi; Bosede Olukemi Lawal (Journal of Agricultural Extension, 2023)
This study examined the gaps and gains of WAAPP interventions on farmers' agricultural productivity in IAR&T-adopted villages of southwest Nigeria. Purposively, 4 adopted villages where the WAAPP project was implemented were selected and a total of 138 farmers were interviewed. With the use of a questionnaire, the study assessed the impact of WAAPP project on the specific agricultural needs of villages, determined agricultural productivity for crop and livestock enterprises and identified challenges associated with the intervention. Linear regression model, variance analysis, and t-test were used to achieve the study objectives. Major gaps identified in WAAPP activities were inconsistencies in operation ( = 2.36), limited market access ( = 2.35) and poor communication with members ( = 2.35). Significant differences also existed in the impact of WAAPP intervention among villages (F= 5.103), and enterprise type (F=4.553). Sex (? = 0.373), age (? = 0.312) and enterprise type (? = 0.365) were major contributors to productivity in WAAPP. The paper concludes that WAAPP interventions in adopted villages positively impacted beneficiaries, though constrained by inconsistencies in operation, intra-communication and limited market access. The study recommends continuous funding and monitoring of agricultural activities by WAAPP to broaden the impact of the intervention.